'I feel like my house was taken away from me': Parents' experiences of having home adaptations for their medically complex, technology‐dependent child. (17th June 2022) - Mitchell, Tracy Karen; Bray, Lucy; Blake, Lucy; Dickinson, Annette; Carter, Bernie
Abstract: Technology‐dependent children are a sub‐population of seriously ill children with life‐limiting conditions who are being cared for at home by their families. Although home‐based care has been the model of care for these children since the late 1980s, there is a paucity of literature about parents' experiences of having home adaptations made to enable their home to be a place of care for their child. Using the findings from auto‐driven photo‐elicitation interviews conducted between August 2017 and June 2018 with 12 parents (10 mothers and 2 fathers) who have a technology‐dependent child (aged 5–25 years) living in England, Scotland and Wales and David Seamon's five concepts of at‐homeness (appropriation, at‐easeness, regeneration, rootedness and warmth) as a conceptual framework, this paper addresses how parents' experienced home adaptations. Thematic analysis generated a meta‐theme of 'Home needs to be a home for all family members' and the three key themes: (1) 'You just get told' and 'you're not involved'; (2) It's just the 'cheapest', 'quickest', 'short‐term' approach; (3) Having 'control' and 'thinking things through.' The need to involve parents in decision‐making about adaptations that are made to their home (family‐informed design) is clear, not only from a cost‐saving perspective for the state, but for creating an aesthetic and functional home that optimises health, well‐being and feelings of at‐homeness for the entire family.